Banking Malware Attacks and Security Solutions Review - Kaira Milani Fitria (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2023)
This research explores the growing threat of banking malware attacks and the security solutions that can be implemented to mitigate the risks. The paper begins by providing an overview of the different banking malware attacks, including their propagation methods and the damage they can cause. It then delves into the various security measures that can be taken to prevent and detect these attacks, such as endpoint protection, network segmentation, and user education. The paper also examines the challenges and limitations of these security solutions and the potential for future developments in the field. Overall, this paper provides a comprehensive analysis of the current banking malware attacks and the security solutions that can be employed to safeguard against them. This research aims to comprehensively analyse the different types of banking malware attacks and the security solutions that can mitigate the risks. By understanding the nature of these attacks and the effectiveness of various security measures, this research can help financial institutions develop more effective strategies for protecting themselves and their customers from cyber threats.